2022
DOI: 10.1109/access.2021.3139305
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Users’ Perception on the Current and Potential Educational Value of an Electrical Engineering YouTube Channel

Abstract: Full comprehension of abstract concepts present in engineering education has been usually considered challenging. Engaging multimedia resources have proven to be useful pedagogical aids to increase students' motivation. In fact, already existing dissemination videos might be suitable to fulfill this objective. This research aims to contribute assessing video implications in the enhancement of engineering education quality, through the evaluation of the current pedagogical use of a specific electrical engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
2
9
0
4
Order By: Relevance
“…The objective behind such video-aided harmonization strategy is taking advantage of videos' potential to lower both essential and extraneous cognitive load, as well as promoting generative processing as explained by CTML. A specific series of 9 scientific dissemination videos was created in Sígueme la Corriente, considering key metrics from literature on format and content adequacy as guidelines for their creation, such as explanation quality, audiovisual quality, contents' technical level and rhythm, efficient length, voice and language, or interestingness [11], [19], [34]- [36]. As inclusion criteria, such videos would cover the main topics of Electromagnetism and 3-Phase Circuits, considered as core knowledge for electrical engineering degree and to a degree of complexity that allows students to reach an appropriate entry level to Electrical Machines I subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective behind such video-aided harmonization strategy is taking advantage of videos' potential to lower both essential and extraneous cognitive load, as well as promoting generative processing as explained by CTML. A specific series of 9 scientific dissemination videos was created in Sígueme la Corriente, considering key metrics from literature on format and content adequacy as guidelines for their creation, such as explanation quality, audiovisual quality, contents' technical level and rhythm, efficient length, voice and language, or interestingness [11], [19], [34]- [36]. As inclusion criteria, such videos would cover the main topics of Electromagnetism and 3-Phase Circuits, considered as core knowledge for electrical engineering degree and to a degree of complexity that allows students to reach an appropriate entry level to Electrical Machines I subject.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis helped to design a specific series of didactic videos that were published in a YouTube channel serving both educational and scientific dissemination purposes, which were subsequently distributed among the students of "Electrical Machines I" of the Electrical Engineering BSc from the School of Industrial, Aerospace and Audiovisual Engineering of Terrassa (Universitat Politècnica de Catalunya) [30]. The selected channel is Sígueme la Corriente [31], which has been studied in previous exploratory research, and has been found potentially suitable for educational use based on users' perception about key metrics related to content and format adequacy [11], [32]. This research extends through three academic years, and addresses the following research questions with a Mixed Methods approach:…”
Section: Introductionmentioning
confidence: 99%
“…Investigaciones previas han evaluado la utilidad de los videos por estudiantes universitarios, encontrando una respuesta notablemente positiva (Gerhart, & Anderton, 2020;Jill et al, 2019;Lijo et al, 2022;Lozano et al,2020;Vera et al, 2019). Se han estudiado patrones, hallando que la experiencia previa tiene un efecto positivo en la Utilidad Percibida (UP) (Giannakos et al, 2016).…”
Section: Innoeduca International Journal Of Technology and Educationa...unclassified
“…y sus profesores) muestran su intención de seguir utilizándolas para aprender (enseñar) matemáticas, en sintonía con lo expuesto porVera et al (2019), Jill et al, (2019,Lozano et al, (2020), Gerhart y Anderton (2020) yLijo et al (2022). El análisis expuesto por ellos en los grupos de discusión avala las investigaciones de Bhatia y Naidu (2017),Dale y Pymm (2009),Evans (2008),Scagnoli et al (2015) y Roque (2020), identificando como primeras ventajas la disponibilidad de las VC, la autonomía que les aportan para verlas las veces que precisen, avancen o retrocedan sobre ellas.…”
unclassified
“…These modules were provided as out-of-class supplementary videos for students in a "Statics and Dynamics" course. Finally, Lijo et al [42] assessed the pedagogical utility of an electrical engineering YouTube channel to enhance the education equality of engineering students through a 5-point Likert scale survey of the channel's audience. These studies have established that supplementary materials that promote self-paced learning significantly improve the learning outcomes of engineering students, with one study [42] specifically mentioning cognitive load.…”
Section: Supplementary Materials In Engineering Educationmentioning
confidence: 99%